2013
DOI: 10.23907/2013.014
|View full text |Cite
|
Sign up to set email alerts
|

Death Certificate Surveillance: A Component of Death Investigation

Abstract: Introduction Medical examiners/coroners serve various functions beyond the medicolegal framework, including making contributions to public safety and health. In order to effectively fulfill this role, it is essential to ensure accurate certification of each death. Materials and Methods In Vermont, the Department of Health, Vital Records Division has developed a death certificate surveillance program in which all registered deaths are reviewed by the Office of the Chief Medical Examiner (OCME). A death certif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…5 The accuracy of the death certificate is paramount, but several studies have demonstrated that errors in certification are common. 4,[6][7][8][9][10][11][12][13][14][15][16] In New York City, inaccurate cause of death on certificates led to inaccurate health disparity tracking. One study of death certificates in 2008 revealed that the disparity in premature heart disease between white and black people in New York City was underestimated because hospitals that incorrectly overreported premature heart disease served larger proportions of white people than black people.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 The accuracy of the death certificate is paramount, but several studies have demonstrated that errors in certification are common. 4,[6][7][8][9][10][11][12][13][14][15][16] In New York City, inaccurate cause of death on certificates led to inaccurate health disparity tracking. One study of death certificates in 2008 revealed that the disparity in premature heart disease between white and black people in New York City was underestimated because hospitals that incorrectly overreported premature heart disease served larger proportions of white people than black people.…”
mentioning
confidence: 99%
“…5 The accuracy of the death certificate is paramount, but several studies have demonstrated that errors in certification are common. 4,6 16…”
mentioning
confidence: 99%
See 1 more Smart Citation